Tingkat Kesejahteraan Rumah Tangga Generasi Kedua Pemukim Kembali di Desa Koto Mesjid Kecamatan Kampar Provinsi Riau - Tince Sofyani; Clara Yolandika (JURNAL SOSIAL EKONOMI PESISIR, 2021)
The objectives of this study were to assess : the level of household welfare of the second generation in Koto Mesjid Village.This study was conducted in Koto Mesjid Village Subdistrict XIII Koto Kampar, Kampar District, Riau Province. Location in this study was selected by purposive sampling technique. Population used in this study were all second generation of married household in Koto Mesjid Village. The number of samples in Koto Mesjid village were 62 households.. The result of this study showed: some of the households in the Koto Masjid were classified as poor households. . The resettlement impacts caused the women's (wife) access to the land to be reduced, caused by the loss of farming activities in the paddy fields as a result of the Koto Panjang dam construction. The poverty experienced by households in Koto Masjid village was largely due to limited land ownership.